18. Yakuza sebagai Kendala Jepang dalam Upaya Memerangi Sex Trafficking - Muhammad Rifqi; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Japan has a very serious problem about Sex Trafficking crime. Sex Trafficking in Japanitself then widened into prostitution and this business is almost entirely controlled by theYakuza, the Japanese mafia. Government of Japan became aware of this problem when thephenomenon of Sex Trafficking emerges. In this research, it is explained that in 2004Japan formulated Action Plan program to address the issue of Sex Trafficking in thecountry. Action Plan program which it purpose is to suppress Human Sexual Trafficking inthe country, formulated efforts made by the Government of Japan are to establish aconnection with another country, tightened